A statistical study on promoting effects of tropical cyclones over the Bay of Bengal on the South China Sea summer monsoon onset - Xiaoting Fan; Ying Li (Atmospheric Science Letters, 2023)
Abstract The onset date of the South China Sea (SCS) summer monsoon (SCSSM) and the generation time of the first tropical cyclone (TC) over the Bay of Bengal (BoB) during late April and early June were significantly correlated with a correlation coefficient of 0.58 during 1979–2020. The composite analysis found that under the impact of BoB TCs, an enhanced southwesterly low‐level flow transported abundant moisture from the BoB to the northern SCS. Besides, the diabatic heating related to TC convection stimulated an anticyclonic anomaly in the upper troposphere over the southern Tibetan Plateau, which was conducive to the enhancement and expansion of the South Asian high (SAH) over the Indo‐China Peninsula. The stronger easterly outflows from the eastern periphery of the SAH overlapped with low‐level water vapor convergence over the northern SCS, enhancing the development of monsoon convection. Thus, more condensation heating warmed the tropospheric atmosphere and reversed the meridional temperature gradient over the SCS, implying the SCSSM onset.